Clothing Color and Pattern Recognition for Impaired people (International Journal of Engineering and Computer Science, 2017)
- In the study of Human-computer-interaction (HCI) the design and use of technology using digitalized computer systems mainly focusing on the particular interfaces between people and computers. There is an ongoing research that taking place till today using Human-computer-interactions especially on visually impaired people. This system mainly introduces the thematic study on “Blind and visually impaired people Human computer and access to Graphics” represents a current research study towards solution for impaired people and brings together a new researchers and practitioners. Here, we are approaching one of the methods which can be useful for the visually impaired people in the form of recognising the clothing patterns. Choosing clothing pattern is one of the challenging tasks for visually impaired people. We matured a camera-based model to notice the clothing patterns. The clothing patterns are categories as five types like (plaid, striped, pattern less, horizontal-vertical, irregular etc) and it identifies 11 clothing colors. The system mainly integrates with the microphone, camera, Bluetooth, earpiece for audio signal. The output of our system is given by audio signal. To recognize clothing patterns, we propose a Hough line Transformation for the detection of pattern and canny detection for detection of edges in the clothing pattern. we proposed the CCNY Clothing Pattern dataset and other different pattern datasets to our method. Using various other performances our method is under the study. In this project we are using OpenCV library for capture the images. Thought such a system would support more independence in blind person’s daily life.